Sand Mold Design for Casting Recycled Aluminum Pots: An Improved Process from Artisanal Methods - Samon, Jean Bosco (Journal of Advanced Research in Mechanical Engineering and Technology, 2022)
The artisanal molding of recycled aluminum pots with green sand is a molding process based on the craftsman’s personal experience. Our study consists in proposing to craftsmen an improved process of local molding aluminum pots. This activity often based on the craftsman’s subjective sizing experience, sometimes, causes casting failures without a valid explanation or justification. To achieve a more improved process of artisanal casting of aluminum pots, we have illustrated two complete casting processes using two shapes of pots widely used at the local level: To control the casting variables such as the shape of the molds, the controlled filling and cooling rates to minimize molding defects, we used basic engineering principles based on the sizing of the mold, in particular, the pouring system (filling pocket, sprue section, channel section, gating system section) and feeding system (riser). To do this, we presented the artisanal process used by craftsmen. The optimized sizing allows the production of rigid pots and good qualities of mechanical properties. This new approach also makes it possible to reduce recurring defects and hardship of workers to increase the profit of tiny businesses. How to cite this article: Samon JB. Sand Mold Design for Casting Recycled Aluminum Pots: An Improved Process from Artisanal Methods. J Adv Res Mech Engi Tech 2021; 8(3&4):13-29.